Innate Immune Response Against Batai Virus, Bunyamwera Virus, and Their Reassortants - David D. J. A. Zöller; Josefin Säurich; Julia Metzger; Klaus Jung; Bernd Lepenies; Stefanie C. Becker (Viruses)
Orthobunyaviruses (OBVs) represent a diverse group of RNA viruses, encompassing a progressively increasing number of arboviruses that cause disease in both humans and livestock. Yet, studies investigating these viruses remain scarce despite the critical importance of such knowledge for assessing their zoonotic potential. In this study, we conducted an evaluation of the early immune response against the understudied Batai virus (BATV), as well as the influence of reassortment with the Bunyamwera virus (BUNV) on this response. Using RNA sequencing of infected murine bone marrow-derived dendritic cells, complemented by qPCR assays, we assessed the innate immune response at the transcriptome level. Additionally, we extended the qPCR analysis by including human THP-1-derived dendritic cells and ovine SFT-R cells to identify differences across species. Our results provide the first evidence that BATV elicits a strong innate immune response compared to BUNV, which largely evades early detection. Reassortants exhibited intermediate phenotypes, although unique changes in the early immune response were found as well. These findings provide a starting point for a better understanding of the immune response to BATV. Furthermore, they raise the question of whether reassortment induces changes in the innate immune response that might contribute to the differences in pathogenicity between reassortant OBVs and their parental generations.